Psychometric Properties of the Generalized Anxiety Disorder Scale Among Saudi University Male Students - Alghadir A; Manzar MD; Anwer S; Albougami A; Salahuddin M (Neuropsychiatric Disease and Treatment, 2020)
Ahmad Alghadir,1 Md Dilshad Manzar,2 Shahnawaz Anwer,1,3 Abdulrhman Albougami,2 Mohammed Salahuddin4 1Rehabilitation Research Chair, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia; 2Department of Nursing, College of Applied Medical Sciences, Majmaah University, Majmaah, Saudi Arabia; 3Department of Building and Real Estate, Hong Kong Polytechnic University, Kowloon, Hong Kong SAR; 4Department of Pharmacy, College of Medicine and Health Sciences, Mizan-Tepi University (Mizan Campus), Mizan-Aman, EthiopiaCorrespondence: Shahnawaz Anwer Email anwer_shahnawazphysio@rediffmail.comBackground: Various screening tools have been designed and developed to identify individuals with generalized anxiety disorder (GAD). The current study aimed to assess the psychometric validation of the GAD-7 in Saudi university male students.Methods: Healthy university male students (n= 192) participated in this cross-sectional study. All the participants were informed about the study details. Participants were asked to complete the GAD-7, the Sleep Hygiene Index (SHI), Perceived Stress Scale (PSS), and demographic details.Results: In general, the range of the GAD total score was 0– 21. There was no issue of the ceiling or floor effects as only 12.5% of participants reported the minimum score of 0, and none of the participants reported the maximum score of 21. The internal consistency score of the GAD-7 was found to be good (Cronbach’s alpha = 0.83). The internal homogeneity between item scores was 0.22– 0.57 as indicated by the “Spearman correlation coefficient (r)”. The total scores and individual item scores of the GAD-7 were statistically associated with the PSS total score (correlation coefficient r = 0.21– 0.37), and scores of the 8th and 13th item of the SHI (correlation coefficient r = 0.17– 0.26, and 0.21– 0.40, respectively). The exploratory factor and confirmatory factor loadings of the GAD-7 items were ranged from 0.60 to 0.81 and 0.51 to 0.80, respectively.Conclusion: This study supported the use of the GAD-7 to assess the anxiety level among Saudi university students.Keywords: GAD-7, anxiety, stress, university students, validity, reliability